SOCIAL CONFLICT DUE TO THE CONTROVERSY OF MOSQUE’S QIBLA DIRECTION IN SEJIRAM VILLAGE, SAMBAS REGENCY - Reza Akbar; Asman Asman (Jurnal Ilmiah Al-Syir'ah, 2020)
Determination of the direction of Qibla precisely becomes very important, especially when preparing for the construction of a mosque. A mosque that the course of Qibla can determine deviates from its intended direction; this is because of many factors, such as measurement and calculation errors, tool use errors, or errors due to the construction of the Mosque. Deviation in the direction of Qibla of a mosque can cause social conflict, such as happened in Sejiram Village, Sambas Regency, in 2010-2011. This study aims to describe the social conflict that occurred in Sejiram Village due to the controversy of the direction of the Mosque’s Qibla and its impacts. This research is qualitative research with a pattern of field research through in-depth interviews to obtain primary data. Based on this research, it found that young people wanted a change in the direction of the Mosque’s Qibla after it proved to the deviant. On the other hand, older people rejected it. The social conflict has an impact on the loosening of relations between parties who got involved in the conflict. However, this conflict turned out to have a positive effect, namely increasing public knowledge about the importance of accuracy in Qibla direction, encouragement to increase understanding in worship, and slowly reducing traditions that not suggested in Islam.